Capacitative (store-operated) calcium entry - Putney, Jim (Henry Stewart Talks, 2007)
The concept of capacitative or store-operated calcium entry, Icrac, Pharmacology of store-operated entry, Theories of activation mechanisms, CIF, Stim1, TRP channels
Archived at 2020/08/13